Combined Ascending Aortic Stent-Graft and Inner Branched Arch Device for Type A Aortic Dissection. (October 2018) - Law, Yuk; Tsilimparis, Nikolaos; Rohlffs, Fiona; Makaloski, Vladimir; Debus, E. Sebastian; Kölbel, Tilo
Purpose: To report the use of the Zenith Ascend stent-graft in conjunction with the Zenith inner branched arch device to treat type A aortic dissection.Case Report: Five patients (mean age 66 years, range 52–78; 4 men) with type A aortic dissection (2 acute) and insufficient distal landing zones were treated with the Zenith Ascend stent-graft and inner branched arch devices to extend the distal landing zone. Left carotid–subclavian bypass was performed in a staged or simultaneous setting depending on the urgency of the condition. Technical success (no type I or III endoleak and successful revascularization of all supra-aortic vessels) was achieved in all patients. Median intensive care unit stay was 5 days (range 4–23) and the median hospital stay was 16 days (range 8–25). The 2 patients with acute dissection died in hospital and at 5 months, respectively. The 3 elective patients were followed for 7, 13, and 19 months, respectively. All had false lumen thrombosis with either a reduced or stable aneurysm diameter.Conclusion: This limited experience demonstrated the feasibility and safety of the combined use of the Ascend stent-graft and inner branched arch devices. This strategy may sometimes be more beneficial than either stent-graft used alone.